The path to national leadership: an understanding of the 25-year formation of the Institute of Higher Education of the National Academy of Educational Sciences of Ukraine - Володимир Луговий (Філософія освіти, 2024)
In the article, from the positions of the director (2006-2012), part-time chief researcher and member of the academic council (since 2006), national higher education reform expert (since 2009), the features of the 25-year history of Institute of Higher Education of the National Academy of Educational Sciences of Ukraine, which founded in the context of global, regional and national development of higher education, its quantitative growth and qualitative enrichment, efficiency of activity are considered. The stages and aspects of the modernization of the institutional mission (goal) and the corresponding status and structural reformatting of the institution as a national leader in systematic research in the university sphere are highlighted. The most important fundamental achievements obtained with the author’s participation and relevant for the science of universities (university studies), that born in the institute, as well as for creation of leadership universities as locomotives of progress, are noted. With regard to European integration, the scientific support for the development of the European Higher Education Area according to the Bologna process, Ukraine’s participation in them, in particular in two key dimensions: 1) compatibility and comparability and 2) competitiveness and attractiveness, and the spread of international cooperation and communication of the institute’s scientists, are characterized. Regarding national self-identification and self-sufficiency, ensuring state sovereignty, the contribution of scientists of the institution to the justification of the principles of increasing the competitiveness of Ukrainian universities and the development of a strategy for creating world-class universities is shown. It was concluded that the research activity of the staff of the scientific institution is important for the approaching victory in the war started by the russian federation, increasing the defence capability and security, post-war innovative recovery and European integration of Ukraine.